2019
DOI: 10.1002/jcb.28914
|View full text |Cite
|
Sign up to set email alerts
|

Phase‐shifted pentafluorobutane nanoparticles for ultrasound imaging and ultrasound‐mediated hypoxia modulation

Abstract: The integration of ultrasound (US) contrast enhancement with oxygen‐loading nanoagents provide the synergistic strategy for simultaneously US imaging and hypoxic microenvironment modulation. Herein, we synthesize pentafluorobutane (PFB)‐loading methoxy poly(ethylene glycol)‐b‐poly(l‐lactide) (PLLA) nanoparticle as the novel US‐contrast‐enhanced agent and demonstrate that PFB@PLLA effectively loads oxygen. We characterize the nanosize, phase‐transformation property and oxygen‐loading amount of PFB@PLLA and inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…[41] For example, Chen et al successfully constructed an "oxygen-carrying" nanoplatform (PFB@PLLA) capable of releasing O 2 in response to ultrasound stimulus by encapsulating methoxy poly(ethylene glycol)-b-poly(l-lactide) (mPEG-PLLA) shell onto liquid pentafluorobutane (PFB) core (Figure 4A). [42] Experiments demonstrated that PFB@PLLA released a large amount of oxygen at the tumor site with ultrasound stimulus, effectively downregulating hypoxia-related proteins (HIF-1 and carbonic anhydrase IX (CAIX)) and glycolysis-related proteins (HK2 and GLUT1), and thereby reducing lactate production (Figure 4B,C). "Oxygen-generating" nanomaterials are a class of materials that can induce oxygen-production reactions in the TME (with overexpressed H + and H 2 O 2 ), mainly including selfdecomposition oxygen-production (CaO 2 , [43] Au 2 O 3 , [44] etc.)…”
Section: Relieving Hypoxiamentioning
confidence: 99%
See 2 more Smart Citations
“…[41] For example, Chen et al successfully constructed an "oxygen-carrying" nanoplatform (PFB@PLLA) capable of releasing O 2 in response to ultrasound stimulus by encapsulating methoxy poly(ethylene glycol)-b-poly(l-lactide) (mPEG-PLLA) shell onto liquid pentafluorobutane (PFB) core (Figure 4A). [42] Experiments demonstrated that PFB@PLLA released a large amount of oxygen at the tumor site with ultrasound stimulus, effectively downregulating hypoxia-related proteins (HIF-1 and carbonic anhydrase IX (CAIX)) and glycolysis-related proteins (HK2 and GLUT1), and thereby reducing lactate production (Figure 4B,C). "Oxygen-generating" nanomaterials are a class of materials that can induce oxygen-production reactions in the TME (with overexpressed H + and H 2 O 2 ), mainly including selfdecomposition oxygen-production (CaO 2 , [43] Au 2 O 3 , [44] etc.)…”
Section: Relieving Hypoxiamentioning
confidence: 99%
“…Reproduced with permission. [42] Copyright 2019, Wiley-VCH. D) Schematic design of the PLANT nanosystem fabricated by vegetable thylakoid and various nanoparticles.…”
Section: Relieving Hypoxiamentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of perfluorocarbon (PFC) NPs and ultrasonic stimulation of oxygen transport provide a new strategy to solve these problems. Based on this, Chen et al (2019) designed PFC‐loaded NPs as ultrasound contrast agents for oxygen‐carrying regulation of anoxic tumors. The synthesized phase‐deformable nano‐agent (PFC@PLLA) was composed of liquid PFC core and methoxy poly(ethylene glycol)‐b‐poly( l ‐lactide) shell, which effectively released oxygen under the stimulation of ultrasound, thus inhibiting the accumulation of HIF‐1 along with its downstream cytokines including VEGF and glucose metabolic factors (HK2 and GLUT1), indicating an effective approach to alleviate the anoxic microenvironment of cancer cells and affect glycolysis as well.…”
Section: Nanomaterials For Inhibition Of Hif‐1 By Regulating Gas Infu...mentioning
confidence: 99%
“…The synthesized phase‐deformable nano‐agent (PFC@PLLA) was composed of liquid PFC core and methoxy poly(ethylene glycol)‐b‐poly( l ‐lactide) shell, which effectively released oxygen under the stimulation of ultrasound, thus inhibiting the accumulation of HIF‐1 along with its downstream cytokines including VEGF and glucose metabolic factors (HK2 and GLUT1), indicating an effective approach to alleviate the anoxic microenvironment of cancer cells and affect glycolysis as well. Therefore, the combination of bifunctional PFC@PLLA nano‐agents with ultrasonic imaging has a synergistic effect in improving ultrasonic efficiency and oxygen‐carrying capacity (Chen et al, 2019).…”
Section: Nanomaterials For Inhibition Of Hif‐1 By Regulating Gas Infu...mentioning
confidence: 99%